Sir John and Lady Rita Cornforth: A Distinguished Chemical Partnership. (September 2015) - Purchase, Rupert; Hanson, James R.
This review describes the life of Sir John Cornforth AC CBE FRS, who was awarded the Nobel Prize for Chemistry in 1975. It covers his early life in Australia, his work in Oxford, the National Institute for Medical Research, the Milstead Laboratory of Chemical Enzymology and the University of Sussex, together with the contributions made by his wife, Lady Rita Cornforth.